Research status and hotspots of hypothermia and human diseases: a bibliometric analysis - Li, Wei-Xuan; Han, Na-Na; Ji, Qian-Yu; Dong, Xue-Tong; Lu, Chao-Long; Wang, Song-Jun (Frontiers in Medicine, 2025)
BackgroundHypothermia has been strongly associated with human diseases; it affects life safety. Therapeutic hypothermia generates good results for certain diseases, without serious complications. In clinical practice, research on the treatment of hypothermia and severe hypothermia-induced diseases have achieved fruitful results. However, no bibliometric analysis has been conducted. In this study, we explored the research status and hotspots of hypothermia and human diseases by conducting a bibliometric analysis.MethodsArticles on hypothermia and human diseases were collected from the Web of Science Core Collection. From 1 January 2005 to 31 August 2024, A total of 1,553 articles were retrieved. After excluding irrelevant articles, 706 articles were analyzed.ResultsThe United States and China published the maximum number of research articles on hypothermia and human diseases. Among institutes, Johns Hopkins University and Harvard University published the maximum number of research articles. Scholars, including Ishikawa Takaki, Maeda Hitoshi, and Michiue Tomomi, constituted a highly productive group of authors. The journal, Therapeutic Hypothermia and Temperature Management published the highest number of articles, and Nature Reviews Drug Discovery had the highest impact factor. Cluster analysis of all keywords primarily focused on the following research directions: (i) hypothermia-related injury, (ii) hypothermia treatment, and (iii) the mechanism underlying hypothermia.ConclusionThis bibliometric study comprehensively summarizes the impact of hypothermia on human diseases and the research overview of the use of moderate hypothermia for treatment. This paper clarifies the research status, frontiers and hotspots, and also puts forward new insights for hypothermia research: strengthen research cooperation to improve the depth of research, increase support for areas with insufficient medical conditions; in the future, single-cell multiomics technology will be used to explore cell types sensitive to different low temperatures and corresponding molecular mechanisms; non-coding RNA regulation will be used to achieve precision treatment of hypothermia diseases; Organoids will be an important object of hypothermia research. These research insights can provide reference for researchers.